2020
DOI: 10.47067/real.v3i2.68
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Traditional and Competency Based Curricula: Perspective of Graduates, Trainers and Employers

Abstract: Traditional training system of TVET sector is focusing on traditional procedures of learning and is based on the numbering system. Such old fashioned procedures and the numbering system are producing certificate holders who do not have proper skills to complete the tasks independently in a professional manner as per the requirements of the industry. Traditional training is not paying focus on the competency oriented workforce in Pakistan. To meet rapid technological changes and need of modern era, the approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Okolocha (2012) advocated that TVET education systems experienced massive alteration recently, because new policies has been imposed under-developed countries to change their traditional TVET rules and practices on CBE. Siddique, Lodhi, Anwer, and Zubair (2020) found that the conventional approach of TVET concentrating on the processes of learning, through rote memorization for achieving grade, that produce TVET graduates who does not have skills, resulting industry mismatch, become burden over the nation. To meet rapid technological changes, TVET sector must shift from conventional to CBT oriented programs.…”
Section: Competency Based Training (Cbt)mentioning
confidence: 99%
“…Okolocha (2012) advocated that TVET education systems experienced massive alteration recently, because new policies has been imposed under-developed countries to change their traditional TVET rules and practices on CBE. Siddique, Lodhi, Anwer, and Zubair (2020) found that the conventional approach of TVET concentrating on the processes of learning, through rote memorization for achieving grade, that produce TVET graduates who does not have skills, resulting industry mismatch, become burden over the nation. To meet rapid technological changes, TVET sector must shift from conventional to CBT oriented programs.…”
Section: Competency Based Training (Cbt)mentioning
confidence: 99%